Reliable free flaps using the microscopic parachute end-to-side technique in severe extremity injuries. Issue 12 (December 2020) - Motomiya, Makoto; Watanabe, Naoya; Kawamura, Daisuke; Yasui, Keigo; Adachi, Akira; Iwasaki, Norimasa
Summary: Purpose: Although end-to-side anastomosis is an essential method for the transfer of free flaps in traumatic extremity injuries, orthoplastic surgeons have no standard technique for performing this procedure. We describe a simple and reliable end-to-side technique is modified from that commonly used by cardiovascular surgeons for free-flap transfer. Methods: Our microscopic parachute end-to-side technique consists primarily of two simple steps. First, the donor vessel is cut and widened with microscissors, and a wide slit is made in the recipient vessel. Second, the heel of the vessel is sutured using the parachute technique, followed by suturing of the vessel wall with a continuous suture to control blood leakage from the widely opened window. We retrospectively evaluated the clinical outcomes of 18 flaps in which the microscopic parachute end-to-side technique was used for both arterial and venous anastomoses. Results: All microscopic parachute end-to-side procedures achieved flap survival without complications related to anastomosis. The mean size of the vesselotomy was 4.8 mm, and the mean expansion rate of the donor vessel was 2.7 times. Conclusions: Compared with the conventional end-to-side technique, the microscopic parachute end-to-side technique has three advantages: easy vesselotomy, avoidance of anastomotic narrowing, and easy control of blood leakage from the anastomotic site. We believe that the microscopic parachute end-to-side technique might make free flaps easier and improve their clinical outcomes in severe extremity injuries.